Comparison of Lemna minor and Spirodela polyrhiza duckweed’s ability to remove cadmium and lead from heavy metals polluted water - Lê, Thị Thanh Trân (2023)
Excluding heavy metals in water using aquatic plants is a recent trend that has attracted a lot of attention due to its effectiveness and environmental friendliness. In this study, the adaptability and accumulation of cadmium and lead in polluted water environments by Lemna minor (L) and Spirodela polyrhiza (S) collected in Dalat (Lam Dong) – LDL, SDL and Phan Thiet (Binh Thuan) – LPT, SPT, Vietnam were investigated. The results showed that the adaptability and growth of Lemna minor followed the order: LPT > LDL > SDL > SPT. The study also examined the optimal environmental conditions for the growth of the plant, which were a pH of 8.43, a temperature of 23.57°C, and a growth period of 13.79 days. Furthermore, in a cadmium and lead-polluted environment, both species of plants showed a higher adaptability to lead pollution compared to cadmium pollution. While Lemna minor had a higher ability to accumulate Cd in biomass than Pb, the opposite was observed in Spirodela polyrhiza.